Regulation of Inflammatory Cytokine Storms by Mesenchymal Stem Cells - Wang, Lu; Li, Yun; Xu, Moyan; Deng, Zihui; Zhao, Yan; Yang, Mengmeng; Liu, Yuyan; Yuan, Rui; Sun, Yan; Zhang, Hao; Wang, Heming; Qian, Zhirong; et al. (Frontiers in Immunology, 2021)
Mesenchymal stem cells (MSCs) have been widely used in preclinical and clinical trials for various diseases and have shown great potential in the treatment of sepsis and coronavirus disease (COVID-19). Inflammatory factors play vital roles in the pathogenesis of diseases. The interaction between inflammatory factors is extremely complex. Once the dynamics of inflammatory factors are unbalanced, inflammatory responses and cytokine storm syndrome develop, leading to disease exacerbation and even death. Stem cells have become ideal candidates for the treatment of such diseases due to their immunosuppressive and anti-inflammatory properties. However, the mechanisms by which stem cells affect inflammation and immune regulation are still unclear. This article discusses the therapeutic mechanism and potential value of MSCs in the treatment of sepsis and the novel COVID-19, outlines how MSCs mediate innate and acquired immunity at both the cellular and molecular levels, and described the anti-inflammatory mechanisms and related molecular pathways. Finally, we review the safety and efficacy of stem cell therapy in these two diseases at the preclinical and clinical levels.